PENGARUH LITERASI KEUANGAN, KOMPETENSI SUMBER DAYA MANUSIA, DAN IMPLEMENTASI E-COMMERCE TERHADAP KINERJA UMKM DI KABUPATEN BANTUL - Zairina, Nurul; Pabulo, Azfa Mutiara Ahmad (ITB AAS Indonesia Surakarta, 2024)
This study aims to assess the impact of financial literacy (X1), human resource competency (X2), and e-commerce implementation (X3) on the performance of micro MSMEs (Y). The study employs a quantitative approach and utilizes non-probability sampling techniques. Primary data is collected through questionnaires directly filled out by respondents, while secondary data is gathered from books, journals, and previous research related to the study's focus. The research focuses on MSMEs located in Bantul Regency. The research specifically focuses on MSMEs located in Bantul Regency. Multiple linear regression analysis is utilized as the analytical tool. The findings indicate that financial literacy (X1), human resource competency (X2), and e-commerce implementation (X3) all exert both individual and combined influences on MSMEs' performance (Y). Keywords : Financial Literacy, Human Resources Competency, E-Commerce Implementation, MSMEs' performance.